2015
DOI: 10.1177/1756285615576663
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in the management of persons with multiple sclerosis

Abstract: For decades, persons with multiple sclerosis (MS) were counseled to avoid excessive physical activity and exercise because of concerns about worsening disease activity. Recent studies indicate that, not only can those with MS tolerate physical exercise, but that it is helpful in managing symptoms, preventing complications and comorbidities, and may possibly have neuroprotective actions. This article reviews previous studies on the effects of different exercise protocols in people with MS, and provides summarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 68 publications
(97 reference statements)
3
40
0
Order By: Relevance
“…Based on studies of other patients with chronic diseases, for example RA, MS, and COPD, regular exercise is a cornerstone of care in addition to pharmacological treatment. [6][7][8] Beneficial effects of the training regimen in this study included increased aerobic capacity and changed body composition to less fat and more muscle mass, which is in accordance with earlier studies on weight/body composition outcomes of physical activity. 19 Additionally, high-resistance strength training causes hypertrophy of skeletal muscles, more of arm muscles than leg muscles, in previously untrained individuals.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Based on studies of other patients with chronic diseases, for example RA, MS, and COPD, regular exercise is a cornerstone of care in addition to pharmacological treatment. [6][7][8] Beneficial effects of the training regimen in this study included increased aerobic capacity and changed body composition to less fat and more muscle mass, which is in accordance with earlier studies on weight/body composition outcomes of physical activity. 19 Additionally, high-resistance strength training causes hypertrophy of skeletal muscles, more of arm muscles than leg muscles, in previously untrained individuals.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, this study supports that MG patients with long disease duration do not worsen from a physical exercise regimen. Based on studies of other patients with chronic diseases, for example RA, MS, and COPD, regular exercise is a cornerstone of care in addition to pharmacological treatment …”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggested that exercise therapy may actually impact disease course in persons at risk for MS and after the disease develops, it might be potentially considered as a disease modifying therapy [5]. Nevertheless, the evidence is inconclusive regarding the efficacy of using exercise therapy for the rehabilitation of people with progressive MS.…”
Section: Exercise Therapymentioning
confidence: 99%
“…The use of a standing frame produced significant improvements in passive hip and ankle range of motion and a trend toward improvement in ankle spasticity [1,5].…”
Section: Exercise Therapymentioning
confidence: 99%
See 1 more Smart Citation